Stability and change in achievement goals during the COVID-19 pandemic: Protective factors contributing to motivational resilience - Lin, Zhuqing; Xie, Jianling; Gallo, Katarzyna; Montecillo, Isabella Rae; Epting, Kristieona; Stewart, Samuel; Hynes, Julianna (Asian Journal of Contemporary Education, 2024)
Motivation is the process by which goal-directed behavior is initiated, energized, and sustained. The type of achievement goals endorsed by students is one of the most significant constructs in motivational research in educational contexts. It is often assumed that achievement goal endorsement is stable over time. However, that may have changed given the outbreak of COVID-19. Data were collected from a sample of undergraduate students in China (n = 300) representing various majors and academic classifications. A 2 x 2 achievement goal framework comprising mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance goals was then compared before and during emergency distance education. Our study results revealed that only scores on performance-approach goals decreased significantly across the two learning conditions (t = 11.66, p < .001), suggesting students were less likely to focus on demonstrating competence relative to others during emergency distance education. However, individual differences were detected between high-achievers and low-achievers in terms of performance-approach goal endorsement during emergency distance education. More importantly, scores on mastery-approach goals did not significantly decrease (t = 1.75, p = .08), suggesting students’ intrinsic motivation remained constant during emergency distance education. While technology support did not positively predict mastery-approach goal endorsement during emergency distance education, student-perceived teacher support and physical learning environment were two significant predictors, implying the power of human connection in online learning during COVID-19.